The efficacy of VIPP-V parenting training for parents of young children with a visual or visual-and-intellectual disability: a randomized controlled trial. Issue 5 (3rd September 2018) - Platje, Evelien; Sterkenburg, Paula; Overbeek, Mathile; Kef, Sabina; Schuengel, Carlo
ABSTRACT: Video-feedback Intervention to promote positive parenting-visual (VIPP-V) or visual-and-intellectual disability is an attachment-based intervention aimed at enhancing sensitive parenting and promoting positive parent–child relationships. A randomized controlled trial was conducted to assess the efficacy of VIPP-V for parents of children aged 1–5 with visual or visual-and-intellectual disabilities. A total of 37 dyads received only care-as-usual (CAU) and 40 received VIPP-V besides CAU. The parents receiving VIPP-V did not show increased parental sensitivity or parent–child interaction quality, however, their parenting self-efficacy increased. Moreover, the increase in parental self-efficacy predicted the increase in parent–child interaction. In conclusion, VIPP-V does not appear to directly improve the quality of contact between parent and child, but does contribute to the self-efficacy of parents to support and to comfort their child. Moreover, as parents experience their parenting as more positive, this may eventually lead to higher sensitive responsiveness and more positive parent–child interactions.